DEVOTIONAL SONGS AS EVIDENCE OF A WOMEN'S FRIENDSHIP: MAGDALENA SIBYLLA OF WÜRTTEMBERG‐STUTTGART AND AEMILIA JULIANA OF SCHWARZBURG‐RUDOLSTADT. (October 2014) - Aikin, Judith P.; Woodford, Charlotte; Colvin, Sarah
ABSTRACT Devotional song texts, thousands of which were authored and published in seventeenth‐century Lutheran Germany, can provide evidence for otherwise unrecorded friendship networks among women. The songs and publications of two dynastic women, Duchess Magdalena Sibylla of Württemberg‐Stuttgart and Countess Aemilia Juliana of Schwarzburg‐Rudolstadt, offer clear evidence of the nature of their long‐distance relationship, despite the fact that their correspondence has not survived. That their interchanges over a period of three decades offered the opportunity to confide their concerns to a person distanced from the situation and to receive emotional support is clear in the surviving song texts. In particular, the songs written explicitly for Magdalena Sibylla by Aemilia Juliana show that she solaced her correspondent by assuming her persona in a show of empathy, employing a sort of ventriloquism in order to give Magdalena Sibylla the words with which to voice her woes and converse with her deity. The handwritten original songs and published books containing songs sent by Aemilia Juliana to her friend as gifts then served as sources for the devotional books that Magdalena Sibylla compiled and published.